Design of a paired-weir system for experimental manipulation of environmental flows in streams. Issue 1 (2nd January 2023) - Rosero-López, D.; Cowen, E. A.; Walter, M. T.; De Bièvre, B.; González-Zeas, D.; Flecker, A.S.; Osorio, R.; Dangles, O.
Abstract: Controlled in-stream flow manipulations are challenging but necessary to implement to assess the consequences of real-world flow alterations on aquatic ecosystems. We designed a double v-notch weir system, which was first prototype-tested in a laboratory flume and then in the field. The device diverted instantaneous flows proportionally in a robust way (e.g., 10% of flow in the stream main channel and 90% of flow into the diversion channel). We tested diversions systematically and evaluated how well flows matched our target flow-percentages. This is one of the first ecohydraulic structures designed and tested to experimentally manipulate environmental flows in small upland streams.